Mechanism of human MxA protein action: variants with changed antiviral properties. - Zürcher, T (1992)
Cells respond to treatment with interferons by synthesizing several induced proteins, including one or more structurally related proteins collectively called Mx. Nuclear and cytoplasmic forms of Mx have been described, some of which inhibit virus replication. Human MxA is a cytoplasmic protein that specifically inhibits the multiplication of influenza virus and vesicular stomatitis virus. Here, we describe a mutant MxA protein, MxA(R645), which inhibited influenza virus but was inactive against vesicular stomatitis virus. It differs from wild-type MxA by a Glu to Arg substitution near the carboxy terminus. Like wild-type MxA, and as expected for an Mx protein acting in the cytoplasm, MxA(R645) blocked influenza virus at a step after primary transcription. When moved to the nucleus of transfected cells with the help of a foreign nuclear transport signal, its mode of action changed. Like mouse Mx1, nuclear MxA(R645) interfered with primary transcription of influenza virus, which is a nuclear process. Our results thus define an MxA region that determines antiviral specificity and further demonstrate that nuclear forms of MxA can mimic the action of mouse Mx1 whose natural location is the cell nucleus.